SISTEM PENYEWAAN KAMERA PADA CV. DIPO CREATIVINDO BERBASIS ANDROID - Arif, Muhammad; Cholil, Saifur Rohman (Jurnal Pengembangan Rekayasa dan Teknologi, 2019)
Camera rental business is a business in the field of photography and videography rental services that are currently developing, but in general data management is still done manually. With the increasing number of cameras owned and the increasing number of tenants conducting transactions, the resulting data is managed to be even greater, thus managing data manually is no longer effective and efficient, so as to ensure accuracy in recording transactions, security in data storage, and accuracy and speed in presenting information needs to be built an Android-based camera rental application. Making this camera rental application begins by collecting data relating to the system to be built, then carried out an analysis, and proceed with designing the system based on the results of the analysis, the next step is to write the program in accordance with the design results. After the program has been written, a test will be carried out to ensure that the program is made as expected. The final step of this activity is to create a documentation system that is realized in the form of research reports. The results of this study are an android-based camera rental application which, when implemented, is expected to be able to overcome all problems in data processing in the camera business area